TEACHER SKILLS IMPROVEMENT IN WRITING A LEARNING IMPLEMENTATION PLAN WITH MODEL IMITATION TECHNIQUES THROUGH SUPERVISION ASSESSMENT - Mardianis Mardianis (JURNAL PENDIDIKAN ROKANIA, 2021)
This study aims to find information about the level of teacher skills in writing lesson plans using model imitation techniques through assessment supervision. The design of this research is qualitative research using descriptive method. The object of this research is the teachers of SDN 018 Tandun, totaling 10 people, they are 5 males and 5 females. The data in this study were obtained from the results of learning supervision. The process and all the results of writing a lesson plan. Data collection in this study was carried out by the researchers themselves using observation techniques, using notes, and cameras. To validate the data in this study using the Triangulation technique. Through model imitation techniques, smart teachers can guide other teachers in need. Teachers are motivated to learn and strive to achieve further success. Based on the category of abilities that have been determined in this study, it turns out that for each cycle the results of the teacher's abilities always increase, so that the objectives of this study are achieved, namely teachers who achieve activity abilities and writing skills results are greater than 76% of the existing teachers. From these results it can be concluded that the modeling technique can improve the skills of writing teacher learning implementation plans